LIABILITY FOR SPAMMING IN THE RUSSIAN LEGISLATION: EXPERIENCE OF CRIMINALIZATION, LAW ENFORCEMENT AND LAWMAKING INITIATIVES - A. I. Khaliullin (Russian Journal of Economics and Law, 2011)
The article views the experience of spamming criminalization in the Russian lawmaking practice, and reveals the narrow interpretation of spam as an offence in advertisement distribution. The criminal-legal interpretation of spamming suggests the possibility of using it as a means of various crimes, but not a as an independent offence. During the research the following techniques were used: formal-logical, systemic, comparative and documents study.